The Package Tour Paradox: Contrasting Economic Yields of Mass versus Independent Travelers in Emerging Island Destinations - Pratiwi, Yunisti; Santri, Agi; Emansyah, Fardi (Journal of Tourism Sustainability, 2025)
Post-pandemic tourism recovery necessitates a strategic pivot from arrival statistics to economic yield. This study investigates the micro-economic behaviour of tourists in Belitung, a burgeoning archipelagic destination in Indonesia, by juxtaposing the expenditure patterns of package tour participants against Free Independent Travelers (FITs). Utilising a cross-sectional survey of 399 respondents selected via purposive sampling, the research uncovers a significant expenditure gap. While domestic package tourists demonstrate higher spending stability, a striking paradox emerges within the international segment: independent travellers contribute nearly three times the direct economic yield (IDR 13.5 million) compared to their package-tour counterparts (IDR 5 million). The data reveal that while package tourism minimises leakage through prepaid structures, it limits local economic injection. Conversely, independent travellers exhibit high elasticity in discretionary spending, particularly in local transport and experiential services. These findings challenge the traditional reliance on mass-package models and advocate for a "high-value" strategy supported by digital payment infrastructure and experience-based product diversification.